PENGARUH DISIPLIN KERJA DAN PENGAWASAN TERHADAP KESELAMATAN DAN KESEHATAN KERJA KARYAWAN PADA PT. RIAU CRUMB RUBBER FACTORY PEKANBARU - Sumiati Siregar; Susi Hendriani; Rio Marpaung (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
The research was conducted at PT. Riau Crumb Rubber Factory in Pekanbaru No.63 at Kampung Suka Ramai street road. That aims to determine how Effect of Discipline work and Observation either simultaneously or partially on Safety and Health of Employee Part of Production at PT. Riau Crumb Rubber Factory in Pekanbaru. The population in this research is employee of PT. Riau Crumb Rubber Factory Part of Production in Pekanbaru, which amounts to 153 employee, and the sample is 60 employee. The Analytics Method is Descriptif of Quantitative Method with SPSS 18.00 version. Simultaneous regression test (F test) showed that the independent variables simultaneously disciplines work and observation has a significant influence on safety and health of employee. The magnitude of the effect that the coefficient of determination (R2) by the two variables simultaneously on the dependent variable while the remaining 69%, 31% influenced by other variables not examined. Partial regression results (t test) showed that the dependent variable has an safety and health employee a significant effect on each of the independent variables studied were disciplines work and observation.Keywords: Discipline Work, Observation, and Safety adn Helth Of Employee